Основные положения метода анализа событий для автоматического контроля и слежения за нераспространением радиоактивных материалов - Буртняк, В.М. (Моделювання та інформаційні технології, 2010)
The substantive provisions of events analysis method of which can arise up in the controlled object or environment of his surroundings are examined. This method allows to shorten time of receipt of conclusion about the state of the looked after object with radio-active materials.